(untitled) (International Journal of Food and Nutritional Sciences, 2023)
"We are what we eat" is an old saying. Our nutritional status, health, bodily and intellectual abilities depend upon what we consume and the way we consume it. Since the dawn of mankind, access to high quality food has been a major concern. However, adulteration of food products is one of the major challenges in today’s society.Nearly every possible food product, from milk to fruits, vegetables to grains, is contaminated to some extent. It is estimated that around 22% of foods are adulterated every year. Besides cheating consumers and constituting a considerable economic problem, adulteration of food poses a serious health risk for consumers. Over 200 acute and chronic disorders, ranging from cancer to digestive tract infections, are known to be brought on by food-borne risks.Adulteration of food thus adversely affects the quality of life and its control demands a strong food-defence strategy that addresses the entire food-supply chain. The paper aims to highlight the problem of food adulteration, its modes andimpacts on producers, consumers and food enterprises and to suggest some safety measures to prevent adulteration of food items.